Meningkatkan Nilai Pancasila terhadap Siswa-Siswi di SDN Jetis 3 untuk Menanamkan Jiwa Kewarganegaraan - Rahmatullah, Faisal; Abdurrohman, Ahmad; Hizkia, Ryandhika Risfi; Ramadani, Sintia Dwi; Nafisa, Amalia Putri; Puspito, Agung Nugroho (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This study aims to improve the understanding and application of Pancasila values in 5th grade students at SDN Jetis 3, Bondowoso, as an effort to instill the spirit of citizenship from an early age. The background of the study is based on the importance of character and moral education through the internalization of Pancasila values, considering that there are still many students who only memorize without understanding the meaning and implementation in everyday life. This study uses qualitative methods with a social project approach, including observation, provision of material, discussion, pre-test and post-test, as well as evaluation through interviews with teachers and principals. The results of the activity showed an increase in students ' understanding of the meaning and application of Pancasila values, both in the school and family environment. Active and contextual cultivation of Pancasila values has proven effective in shaping the character, attitude, and behavior of students who are ethical and have a spirit of nationalism. This study recommends collaboration between schools and families in familiarizing the application of Pancasila values to form a young generation with noble character and able to face the challenges of globalization.